موقف الوزير الفاطمي كتيفات من أزمة الحكم بعد مقتل الخليفة الآمر 524 هـ / 1130م - الرويضي، محمود محمد فالح; محاسنة، محمد حسين سلامة (جامعة عين شمس - كلية الآداب, 2005)
تتحدث هذه الدراسة عن الوزير الفاطمي أبى علي أحمد بن الأفضل بن بدر الجمالي، الملقب (كتيفات)، وتتضمن البحث في أحوال الدولة الفاطمية بعد وفاة الخليفة الآمر بأحكام الله سنة ٥٢٤ ه / ١١٣٠ م، حيث تعرضت الدولة لأزمة سياسية بسبب وفاة الخليفة الآمر دون أن يترك وليا للعهد، فلم يكن له أبناء يتولون من بعده. وجاء اختيار الحافظ لدين الله ليكون وليا للعهد لمولود منتظر للآمر، محاولة للخروج من الأزمة، ثم تدخل الجند وألزموا الحافظ بتعيين أبى على أحمد ابن الأفضل وزيرا، فسيطر على إدارة الدولة، وأبعد الحافظ عن الحكم، إذ سجنه ولم يسمح لأحد بالدخول إليه حتى ثار أنصاره، فقتلوا أبا على، وأخرجوا سيدهم الحافظ من السجن، ونصبوه خليفة للدولة الفاطمية سنة ٥٢٦ ه / 1131 م. This study concentrates on the Fatimid minister Abu Ali Ahmad bin al-Afdal bin Badr al - Djamali, nicknamed (Kutayfat), It also, deals with the circumstances of the Fatimid state after the death of the caliph Al- Amer bi- Ahkam Allah in the year 524 A. H\ 1130 A. D, the state faced a political crisis with the death of the caliph, because he did not assign an heir to the throne, because he did not have male children to succeed him. Thus the selection of al- Hafiz Li - Din Allah to be success or to his unborn yet children had been considered as cape haven to this crisis. However this procedure was unacceptable, which forced the army to interfere and forced al- Hafiz to appoint Abu Ali Ahmad bin al-Afdal As minister, hence Abu Ali controlled the state and obliged al- Hafiz to resign, who was imprisoned, and more over he did not let anyone of his followers to see him, a situation pushed his followers to rebel against the vizier, that rebellion resulted in the killing of Abu Ali, and free their master, al- Hafiz from prison, then they appoint him caliph to the Fatimid state in the year 526 A. H /1132 A. D.
Keywords: المشكلات السياسية -- الدولة الفاطمية -- الملوك والحكام -- الأحوال السياسية -- كتيفات ، أحمد بن الأفضل بن بدر الجمالي -- ابن المستعلى ، منصور بن أبي القاسم ، ت 524هـ -- المعارضة السياسية -- الاعتقال -- السجن -- الاغتيال -- المذاهب الفقهية -- الاسماعيلية